Reconfiguration of Circular Microstrip Patch Antenna for Wireless Applications - Premalatha, J; Sheela, D; Abinaya, M (International Journal of Engineering and Technology, 2018)
Reconfigurable antennas provide a possible solution to solve the related problems using the ability to switch frequency, patterns and polarization. This paper represents a possible application in wireless communication using reconfigurable Microstrip patch antenna. The dielectric substrate of proposed circular Microstrip patch antenna is fabricated with FR 4 epoxy and patch design 40x40x1.6mm. This work provides a methodology to design reconfigurable antennas with PIN diode switch. The frequency reconfiguration achieved by PIN diodes At the range of 3 GHZ to 6.9 GHZ the frequency reconfigurability Â is realized. To resonate the antenna at various frequencies PIN diode is used. Simulation of Ansoft HFSS software is used to compute the gain, axial ratio, radiation pattern, and return loss of proposed antenna. The structure of circular patch antenna achieves an enhanced wide bandwidth. The results show a better frequency reconfiguration.Â Â